Review: The Mystical and Prophetic Thought of Simone Weil and Gustavo Gutierrez: Reflections on the Mystery and Hiddenness of God - Pecknold, C. C. (The journal of theological studies, 2003)
The Mystical and Prophetic Thought of Simone Weil and Gustavo Gutierrez: Reflections on the Mystery and Hiddenness of God Alexander Nava xi + 205 Albany, NY State University of New York Press 2001 Hardback$62.50 0 7914 5177 7 Paperback$20.95 0 7914 5178 X